Kebangkitan Islam dan Negara Beberapa Kasus dari Asia Tenggara - Ali-Fauzi, Ihsan (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
Artikel ini merupakan review buku Robert W. Hefner dan Patricia Horvatich (eds.), Islam in an Era of Nation States: Politics and Religious Renewal in Muslim Southeast Asia (Honolulu: University of Hawaii Press, 1997)DOI: 10.15408/sdi.v5i3.743